Recent Progress in Three‐Terminal Artificial Synapses: From Device to System. Issue 32 (11th April 2019) - Han, Hong; Yu, Haiyang; Wei, Huanhuan; Gong, Jiangdong; Xu, Wentao
Abstract: Synapses are essential to the transmission of nervous signals. Synaptic plasticity allows changes in synaptic strength that make a brain capable of learning from experience. During development of neuromorphic electronics, great efforts have been made to design and fabricate electronic devices that emulate synapses. Three‐terminal artificial synapses have the merits of concurrently transmitting signals and learning. Inorganic and organic electronic synapses have mimicked plasticity and learning. Optoelectronic synapses and photonic synapses have the prospective benefits of low electrical energy loss, high bandwidth, and mechanical robustness. These artificial synapses provide new opportunities for the development of neuromorphic systems that can use parallel processing to manipulate datasets in real time. Synaptic devices have also been used to build artificial sensory systems. Here, recent progress in the development and application of three‐terminal artificial synapses and artificial sensory systems is reviewed. Abstract : Recently, various artificial devices have been made to emulate synaptic plastic for neuromorphic computing, and to build artificial sensory and motor systems. This Review summarizes recent progress in three‐terminal artificial synapses from device to system.